Processos históricos ou condições locais: o que governa a estrutura funcional de peixes de riachos neotropicais de diferentes regiões biogeográficas? - Rodrigues Filho, Carlos Alberto de Sousa (Instituto Nacional de Pesquisas da Amazônia - INPA, 2017)
Ecological studies at large scales have used the functional approach as a way of comparing regions with different taxonomic compositions. This approach is based on species characteristics that directly or indirectly affect your fitness. More recently, this aspect of biodiversity has been very important for conservation studies, due to the close relationship between environmental changes and functional diversity. One way of understanding the future is by understanding the past. Thus, identifying the consequences of historical and contemporary disturbances in the current assemblages can guide us in future decision-making. The objectives of this study were: (i) to investigate how local species richness influences functional structure in each region, (ii) to compare the importance of specialist and redundant species for each biome, using a random scenario of species loss, (iii) to evaluate the importance of contemporary and historical factors in the patterns of richness and functional dissimilarity in the Amazonian and Caatinga streams, and (iv) to investigate whether species of the same order present different functional strategies in streams with similar environmental conditions but different evolutionary history. For this, a database of fish assemblages of 69 streams of the Amazon and Caatinga biomes was used. As a result, we find that historical factors show the great importance of the local and regional structure of stream fish assemblages. In combination with contemporary factors, may be able to generate the various idiosyncratic patterns observed in the literature, by selecting different pools of species between regions. Assemblies experiencing long periods of historical instability have high levels of functional redundancy, possibly to resist the constant environmental changes over time. In summary, this study reinforces the importance of assessing historical factors in small and large-scale studies. However, we have also identified a joint action of contemporary and historical effects, suggesting that complex and unidirectional mechanisms (initially historical filters followed by contemporaries) are responsible for governing the functional structure patterns in stream fish assemblages of Amazonian biomes and the Caatinga.
Keywords: Diversidade funcional; Peixes de riachos; Perda de peixes